Population Growth Model and Mortality of Pakistan Lobster (Panulirus polyphagus) in Estuary Waters of Tarakan City - Agus Indarjo; Gazali Salim; Lukman Yudho Prakoso; Budi Pramono; Meiryani; Thonas Indra Maryanto; Suriyanti; Muhammad Firdaus; Rozi (Bogor Agricultural University, Indonesia, 2023)
Lobster Panulirus polyphagus has a fairly high economic value and is found in the estuary waters of Tarakan City. This research aims to study the growth and mortality model of Lobster P. polyphagus originating in the estuary waters of Tarakan City. The research method was carried out using a quantitative descriptive method. Sampling was conducted 14 times from December 2021-May 2022 using gill nets. The results showed that the male sex ratio was more than the female. Allometric growth of males and females is negative allometric with a thin body shape. The structure of the size obtained was mostly in males ranging from 18.3-20.6 cm, and females around 20.5-22.2 cm. The maximum length growth of P. polyphagus based on von Bertalanffy's growth model was 31.519 cm in males and 31.374 cm in females. The total mortality (Z) of P. polyphagus for males and females was 1.104 and 1.119; catch mortality (F) of 0.106 and 0.253; natural mortality (M) of 0.998 and 0.866; exploitation rate (E) of 0.096 and 0.226, respectively. The high natural mortality causes the extinction of the Lobster species, so good management is needed so that it is sustainable.